PS-021 Use of an E-learning program to improve paediatric nurses' dose calculation skills. (24th February 2014) - Fischer, H; Jeffery, L; Nielsen, JL; Nielsen, LR
Abstract : Background: Adverse events associated with poor dose calculation skills among nurses on paediatric wards are frequent and may lead to increased morbidity and mortality. An E-learning program has successfully been implemented in one paediatric ward in Denmark and is used for competency training and revision. Purpose: To evaluate a nationwide up-scaling of an E-learning program on paediatric nurses' dose calculation skills. Materials and methods: The intervention contained training on dose calculation skills using an E-learning program and a teaching session provided by the hospital pharmacy. Nurses in 8 paediatric wards throughout Denmark participated. Dose calculation skills were evaluated by a "before" and "after" test containing 15 generic calculation tasks. Nurse satisfaction with study participation was evaluated by a questionnaire survey. Results: Of the 97 nurses completing the "before" test, only 36 (37%) completed the "after" test and 15 (42%) of those had trained 1 h or less using the E-learning program. The questionnaire was filled in by 55 nurses. The test results showed mean scores of 75.9% (pre-training) and 79.9% (post-training) of correct answers. According to the questionnaire survey, the majority of the nurses reported: improvement in their calculation skills (30 out of 54), satisfaction with the E-learning program (33 out of 36), satisfaction with the teaching lesson (36 out of 41) and satisfaction with the collaboration with the hospital pharmacy (47 out of 53). The majority were positive towards the E-learning program, test and teaching in the future. Conclusions: The study found a tendency to improvement in dose calculation skills among nurses completing both tests, despite only a little training using the E-learning program. The majority of the participants were satisfied with the E-learning program and were positive towards it as a future initiative. However, the study completion rate was low suggesting that the up-scaling model needs further development for successful implementation. No conflict of interest.